The Correlation of Head Nurses’ Time Management with Nurses’ Job Satisfaction in Medical & Surgical Wards of Hospitals in Arak Medical Sciences University - Nasri, Shokofeh; Pazargadi, Mehrnoosh; ZagheriTafreshi, Mansoreh; Nassiri, Navideh (Advances in Nursing & Midwifery, 2013)
Abstract Introduction: Control of time and prevention from wasting time can improve the ability of managing, retaining human resources, decreasing stress and increasing job satisfaction among personnel. Lack of time management in nursing profession may have effect on quality of care and declining efficiency and productivity which lead to feeling burnout and job dissatisfaction in nurses. The aim of this research is to determine the correlation of the head nurses’ time management behaviors with nurses’ job satisfaction. Materials and methods: This research is a descriptive – correlation study. In this research head nurses and nurses who have had inclusion criteria and were employed in medical & surgical wards of hospitals in Arak Medical Sciences University participated by census method. For data collection, two questionnaires about time management and job satisfaction have been designed according to research goals. Their validity were measured by face and content validity (time management: CVI= and job satisfaction: CVI= ) and their reliability by Kronbach - Alpha coefficient ( . and . ). Analyzing data has performed by SPSS software, version . Results: Analysis of data showed that there was not any correlation between time management behaviors of head nurses (from their view) with nurses’ job satisfaction(r = . , p > . ). But the correlation of time management behaviors of head nurses )from nurses’ view( with job satisfaction of nurses was significant (r= . , p< . ). Conclusion: The findings of this research reveal the importance of using time management skills by the nurse managers as a step to improve nursing effectiveness and nurse’ job satisfaction. Keywords : Time Management, Job Satisfaction, Nurse